2007
DOI: 10.1091/mbc.e06-08-0738
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Spc7 Protein Is Required for Spindle Integrity and Links Kinetochore Complexes in Fission Yeast

Abstract: Spc7, a member of the conserved Spc105/KNL-1 family of kinetochore proteins, was identified as an interaction partner of the EB1 homologue Mal3. Spc7 associates with the central centromere region of the chromosome but does not affect transcriptional silencing. Here, we show that Spc7 is required for the integrity of the spindle as well as for targeting of MIND but not of Ndc80 complex components to the kinetochore. Spindle defects in spc7 mutants were severe ranging from the inability to form a bipolar spindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 96 publications
(149 reference statements)
4
44
1
Order By: Relevance
“…The temperature-sensitive Spc7-23 protein is present in the cell at the nonpermissive temperature but is not kinetochore associated (26). We therefore analyzed whether extra sos7 ϩ rescued the temperature-sensitive phenotype of spc7 mutant strains by assisting kinetochore targeting of the mutant Spc7 protein.…”
Section: Identification Of Sos7mentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature-sensitive Spc7-23 protein is present in the cell at the nonpermissive temperature but is not kinetochore associated (26). We therefore analyzed whether extra sos7 ϩ rescued the temperature-sensitive phenotype of spc7 mutant strains by assisting kinetochore targeting of the mutant Spc7 protein.…”
Section: Identification Of Sos7mentioning
confidence: 99%
“…It has been suggested that Kre28 and Zwint are orthologs, although sequence similarities are very limited (48). In this work, we have identified the missing interaction partner of the S. pombe Spc7 protein.Two synergistic microtubule-binding activities exist for the KMN-NMS network, one mediated by the Ndc80 complex via the Ndc80-Nuf2 homodimer and the other by the Spc7-Spc105-KNL-1-Blinkin family, which associates with microtubules via their N-terminal ends (2,26,48,71,73,75). Kinetochore-microtubule interactions are regulated by Aurora B-mediated phosphorylation on several KMN-NMS targets, including the Spc7-Spc105-KNL-1-Blinkin family (4,5,32,72).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1). Interestingly, Spc105/KNL1 is also a kinetochore docking site for the vertebrate checkpoint components Bub1 and BubR1 (Kiyomitsu et al 2007), and is required for proper kinetochore-microtubule attachments in many model systems (Kerres et al 2007;Wan et al 2009). Thus, Spc105-PP1 complexes would be at the right place on kinetochores to regulate and coordinate both checkpoint silencing and kinetochore-microtubule stabilization.…”
Section: Toward the Identification Of Regulators And Substrates Of Ppmentioning
confidence: 99%